2001
DOI: 10.1080/026404101750158330
|View full text |Cite
|
Sign up to set email alerts
|

Muscle power patterns in the mid-acceleration phase of sprinting

Abstract: To assess the role of the lower limb joints in generating velocity in the mid-acceleration phase of sprinting, muscle power patterns of the hip, knee and ankle were determined. Six male sprinters with a mean 100 m time of 10.75 s performed repeated maximal sprints along a 35 m indoor track. A complete stride across a force platform, positioned at approximately 14 m into the sprint, was video-recorded for analysis. Smoothed coordinate data were obtained from manual digitization of (50 Hz) video images and were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
84
1
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(103 citation statements)
references
References 16 publications
16
84
1
2
Order By: Relevance
“…Such IDA approaches have been widely used in an attempt to understand the lower limb RJMs during discrete stance phases in the fastest form of gait, sprinting [1][2][3][4][5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…Such IDA approaches have been widely used in an attempt to understand the lower limb RJMs during discrete stance phases in the fastest form of gait, sprinting [1][2][3][4][5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…2,3 As such, literature reports propulsive forces within acceleration to be 46% greater than those observed within maximal velocity running. [4][5][6] Fundamentally therefore, a large training consideration should be noted for training modalities which provide overload to the propulsive nature of GRF application within the acceleration phase of sprint running.…”
Section: Introductionmentioning
confidence: 99%
“…For the purpose of this study, biomechanical differences between the light and heavy shoe were only considered relevant if they relate to the performance outcome. Previous research and sprinting coaches have mainly suggested the following variables to promote sprint start performance: High vertical and propulsive GRFs [18,19] and high angular velocities of the lower-extremity joints in the sagittal plane [20][21][22], leading to a high concentric joint power (joint moment x joint angular velocity) [5]. Therefore, the input for the SVM was a data matrix containing data rows, of individual trials and data columns of time-normalized waveforms of 11 biomechanical variables: Vertical and anterior-posterior GRFs, and sagittal angular velocities, moments and power of the ankle, knee, and hip joint.…”
Section: Discussionmentioning
confidence: 99%
“…In order to achieve high propulsive forces, athletes have to generate maximum joint power at the hip, knee and ankle joint in a proximal to distal order [5,6,22]. Since the ankle transfers the power generated by the leg to the ground before push-off, it plays an important role for high horizontal sprinting velocities [5]. Therefore, the increase in plantarflexion velocity and corresponding ankle power in the light shoe compared to the heavy shoe during the second 50% of the stance phase might explain the increased sprint start performance in the light shoe.…”
Section: Biomechanicsmentioning
confidence: 99%
See 1 more Smart Citation